P-glycoprotein restricts ocular penetration of loperamide across the blood ocular barriers: a comparative study in Mdr1a knock-out and wild type Sprague Dawley rats. - Tatke, Akshaya (AAPS PharmSciTech, 2018)
The current research was undertaken to determine the existence and magnitude of P-glycoprotein (P-gp) expression on the blood ocular barriers by studying the ocular penetration of loperamide, a specific P-gp substrate, in P-gp (Mdr1a) knock-out (KO) and wild type (WT) Sprague Dawley rats. A clear, stable, sterile solution of loperamide (1 mg/mL), for intravenous administration, was formulated and evaluated. Ocular distribution was studied in P-gp KO and WT rats following intravenous administration of loperamide (at two doses). The drug levels in plasma, aqueous humor (AH) and vitreous humor (VH) samples were determined with the aid of UHPLC- Q-TOF-MS/MS and the AH/plasma (D(AH)) and VH/plasma (D(VH)) distribution ratios were estimated. Electroretinography (ERG), ultrastructural analyses and histology studies were carried out, in both KO and WT rats, to detect any drug induced functional and/or structural alterations in the retina. Dose-related loperamide levels were observed in the plasma of both WT and KO rats. The loperamide concentrations in the AH and VH of KO rats were significantly higher compared to that observed in the WT rats, at the lower dose. However, a marked increase in the D(AH) and D(VH) was noted in the KO rats. ERG, ultrastructure and histology studies did not indicate any drug induced toxic effects in the retina under the test conditions. The results from these studies demonstrate that P-gp blocks the penetration of loperamide into the ocular tissues from the systemic circulation and that the effect is more pronounced at lower plasma loperamide concentrations.